Caracterização físico-química dos latossolos vermelhos para aplicação como pigmento cerâmico natural - Monteiro, Francinara Maria Lobo (Universidade Federal Rural do Semi-Árido, 2018)
Latosols are the most developed soils of the earth's crust. In Brazil, they are widely distributed, occurring practically in all regions of the country. However, the great majority of the researches work on the physical, chemical and mineralogical aspects and their influences on the issues of their management, use and degradation, observing their contributions to the development of food crops. Soil studies such as ceramic pigments are still scarce, not only in Brazil, but in the world; however, there is a growing interest in the pigment ceramics industry, the search for new materials that contribute to the reduction of the environmental impact caused by synthetic methods of production, as well as lower costs, thus reaching a greater number of consumers. This work has as objective the characterization of red latosols of the state of Rio Grande do Norte and its application as pigment in ceramic pieces. Experimentally, the Oxisol sample was initially subjected to treatment to remove impurities by washing and drying. Afterwards, the physical, chemical and mineralogical characterization was performed through soil analysis, fluorescence and x-ray diffraction methods, thermogravimetric analysis, scanning electron microscopy, visible UV spectroscopy and colorimetry. The minerals identified in the x-ray diffractograms were quartz, kaolinite, magnetite, goethite, hematite and illite. X-ray fluorescence revealed a higher percentage for silicon oxide corroborating with the XRD assay. The thermogravimetric curves indicated a small loss of mass, referring to the moisture and decomposition of the organic matter. The images obtained through a scanning electron microscope revealed morphology and dimensions of very heterogeneous particles. According to the diffuse reflectance spectrum, the main chromophore ion of the latosol sample was Iron (III). Samples of the natural and heat treated soil were mixed with the percentages 2, 3 and 5% by mass in the clear transparent enamel and applied on ceramic pieces. The pigments presented shades of pastels to browns, modifying the shade with the percentage and calcination temperature. The best results were obtained with percentages of 5% of pigment and calcination at 800ºC. Finally, the latosols presented themselves as an environmentally correct, economically viable and easily manufactured product as a natural pigment for the ceramic tile and flooring industry
Keywords: Pigmento Natural; Latossolo; Revestimentos Cerâmicos; Natural Pigment; Latosol; Ceramic Coatings; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA